(untitled) (Asian Business Research, 2022)
With the current changes in the trend of digital information technology, the development needs of the macroeconomic market within the new economic development stage and the international diversified economic wave, it is obvious that the financial management system of Chinese enterprises is no longer applicable.Then enterprise to promote intelligent finance, explore innovative enterprise financial management system for the urgent need. In view of the fact that, this article analyzes and discusses the problems belonging to the financial management system of Chinese enterprises at the existing stage, and creates a practicable path for the financial management system in a multi-dimensional and multi-level manner. The management of business operations and financial management is accompanied by a synchronised and optimized system for the management of communities, providing timely integration and dynamic quality enhancement.